Exploring Effective Strategies and Activities to Teach English in EFL Classes - Faizy, Asadullah (Integrated Journal for Research in Arts and Humanities, 2024)
This study is going to explore most effective strategies and activities in order to use them in Afghanistan EFL classes to teach English language skills and elements like reading, writing, speaking, grammar, pronunciation, vocabulary and listening effectively. This study is an experimental design in which the researcher used from the experiences of his participants who are experienced English language instructors in Afghanistan Higher Education. In this study qualitative approach is used and data were gathered by semi-structured interview from four experienced English language instructors. The results indicated that as English language has several skills and elements like Reading, Writing, Speaking, Listening, Vocabulary and Grammar; there are unique or specific strategies and activities for each individual skills and elements to use them in order to teach language effectively in EFL classes.